1989
DOI: 10.1111/j.1365-2125.1989.tb05381.x
|View full text |Cite
|
Sign up to set email alerts
|

Single dose kinetic study of the triple combination mefloquine/sulphadoxine/pyrimethamine (Fansimef) in healthy male volunteers.

Abstract: A single dose pharmacokinetic study of a combined antimalarial formulation of mefloquine, sulphadoxine and pyrimethamine (Fansimef®) has been performed in 10 healthy adult male Malaysian volunteers. The dose consisted of two tablets containing 250 mg mefloquine base, 500 mg sulphadoxine base and 25 mg pyrimethamine base each. Plasma concentrations of mefloquine and pyrimethamine were measured by GC-ECD, those of sulphadoxine by h.p.l.c. Time to peak concentrations (mean ± s.d. for mefloquine (5.70 ± 0.95 h), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
5

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 14 publications
1
18
5
Order By: Relevance
“…No K a or V d values in children have been published previously for either PYR or SDX. For the two drugs, the t 1/2 were in the same general range as those published previously for children (14,17,48) and for adults (1,2,5,6,13,15,17,21,22,23,29,33,44,45), and our results showed wide interindividual variability of both drugs in children. In a review, Butler et al (7) indicated that the V d for many drugs was greater in children than in adults and that elimination may be altered in children compared with adults.…”
Section: Discussionsupporting
confidence: 75%
“…No K a or V d values in children have been published previously for either PYR or SDX. For the two drugs, the t 1/2 were in the same general range as those published previously for children (14,17,48) and for adults (1,2,5,6,13,15,17,21,22,23,29,33,44,45), and our results showed wide interindividual variability of both drugs in children. In a review, Butler et al (7) indicated that the V d for many drugs was greater in children than in adults and that elimination may be altered in children compared with adults.…”
Section: Discussionsupporting
confidence: 75%
“…A recent study indicated that a similar HPLC assay could also be used to measure pyrimethamine levels in infant plasma but did not report any values for infant plasma that had been collected (22). As noted above, the disposition of pyrimethamine in the infants we studied appears to be in the range in adults noted by others (2,7,12,19,20,22). For example, serum pyrimethamine levels in immunologically normal adults while taking a 25-mg (0.3-mg/kg) daily dose (measured with our HPLC assay) ranged from 0.9 to 1.7 ,ug/ml.…”
Section: Discussionmentioning
confidence: 50%
“…For example, serum pyrimethamine levels in immunologically normal adults while taking a 25-mg (0.3-mg/kg) daily dose (measured with our HPLC assay) ranged from 0.9 to 1.7 ,ug/ml. Time to peak levels in Malaysian adult volunteers was found to be 3.3 + 1.98 h and half-life was 114 + 42 h (12), and half-lives in adults have been reported to range from 23 to 175 h (22). As noted above, in a study of human immunodeficiency virusinfected patients, levels with 25-to 75-mg doses for adults (weight not specified) ranged from 260 to 4,471 ng/ml (20).…”
Section: Discussionmentioning
confidence: 99%
“…Despite a prohibitive price making their deployment difficult, artemisinin-based combination therapies (ACTs) are the best antimalarial treatments available nowadays and are recommended by WHO since 2001 (Mutabingwa, 2005). MEF was additive in both studies but it is not an optimal candidate because persistence of subinhibitory concentrations for long periods (elimination t 1/2 , 2 weeks) (Karbwang et al, 1988;Mansor et al, 1989). CQ remains one of the cheapest antimalarial easily accessible in developing countries.…”
Section: Discussionmentioning
confidence: 99%